Is the Slope of the Euro Area Phillips Curve Steeper than It Seems? Heterogeneity and Identification - Johannes Schuffels; Clemens Kool; Lenard Lieb; Tom van Veen (Center for Economic Studies and ifo Institute (CESifo), 2022)
Heterogeneity in Phillips Curve slopes among members of a monetary union can lead to downward biases to estimates of the union-wide slope in reduced form regressions. The intuition is that in a monetary union with heterogeneous regional Phillips Curve slopes, the central bank, aiming at stabilizing demand shocks, will react stronger to shocks in regions with steep slopes compared to shocks in regions with flat slopes. Using a simple New-Keynesian model of a monetary union that omitting controls for this heterogeneity, we show that reduced form estimates of the union-wide slope suffer from a substantial bias towards zero. Empirically, we show that controlling for slope heterogeneity in Euro Area data increases reduced form estimates of the slope in the period since 2009.
Keywords: E24; E31; E58; 330; Phillips curve; heterogeneity; monetary meeting